The impact of profitability ratios toward stock returns: the comparison of top 30 companies listed in Bursa Malaysia and FTSE-100 Index London Stock Exchange / Dorees Priscilla Dok Edward August - Dok Edward August, Dorees Priscilla (2016)
This study has been conducted to determine the impact of profitability ratios toward stock return. Based on previous research, the problem is still present there that what should be the actual impact of firms performance on stock returns. This study is conducted to test the impact of firm‘s performance on stock returns, evidence from top 30 companies listed in Bursa Malaysia and FTSE-100 Index London Stock Exchange over the period 2010-2015. In this study, there are five independent variables and one dependent variable. Earnings per share, Return on Assets, Return on Equity, Net Profit Margin and Gross Profit margin is used as independent variables, while Stock Returns is the dependent variable. Panel regression method is used for the data analysis. Results show that EPS, ROA, ROE, and NPM have no significant impact toward stock return, while only GPM shows positive significant impact toward stock returns.